Chylomicron remnant clearance from the plasma is normal in familial hypercholesterolemic homozygotes with defined receptor defects. - Rubinsztein, D C (1990)
The retinyl palmitate fat tolerance test was used to measure chylomicron remnant clearance in 10 normal subjects (apolipoprotein E [apo E] isotypes 3 or 4 only), 6 normolipidemic apo E2/2 homozygotes and 5 familial hypercholesterolemic homozygotes. Skin fibroblasts with fully upregulated LDL receptors from the latter subjects degraded rabbit 125I-beta VLDL in vitro at rates ranging from less than 10-48% of normal. Experiments in vivo revealed no significant differences between the normal and homozygous familial hypercholesterolemic (FHH) subjects in chylomicron remnant clearance assessed on the basis of "areas under the curves" for retinyl palmitate levels present in post-prandial serum, chylomicron remnants (Sf. less than 1,000), or chylomicrons (Sf. greater than 1,000). Remnant clearance was greatly decreased at all times in the apo E2/2 homozygotes, indicative of an important degree of flux control exerted by a receptor-mediated step involving apo E as ligand. The absence of any excess remnant accumulation in FHH subjects with varying "impairment" of LDL receptor-mediated degradation of apo E-containing lipoproteins, permits the conclusion that chylomicron remnants are initially cleared from the plasma by apo E-recognizing receptors which are genetically distinct from LDL receptors.